Pengaruh Terapi Relaksasi Otot Progresif Terhadap Kualitas Tidur Lansia Di Posyandu Medang Kamolan Kelurahan Banyuanyar Kota Surakarta - Ema Erfiana; Ika Silvitasari (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Background: The increase in the elderly population can have an impact on many health problems in the elderly, one of which is sleep quality problems. Prevelence in Indonesia the incidence of sleep problems at the age of 60 years and more there is a very high number of cases around 67%. Where sleep quality problems in the elderly can lead to type 2 diabetes mellitus and obesity. Non-pharmacological handling in overcoming sleep quality problems can be through progressive muscle relaxation therapy techniques. Progressive muscle relaxation therapy is able to increase feelings of comfort, and psychological relaxation by improving sleep quality in the elderly.Objective: Knowing the effect of progressive muscle relaxation therapy on sleep quality in the elderly at the Medang Kamolan posyandu, Banyuanyar Village, Surakarta City. Method: This study used the Quasi Experiment Design method with the One Group Pre-Test Post-Test Design design. The sampling technique used was non probability sampling technique with a sample size of 20 elderly people and using the Wilxocon test. Results: The results using the Wilxocon test p-value 0.000. Conclusion: There is an effect of progressive muscle relaxation therapy on sleep quality at Posyandu Medang Kamolan, Banyuanyar Village, Surakarta City